The Property of the Nation : George Washington's Tomb, Mount Vernon, and the Memory of the First President - Costello, Matthew (Matthew R.) (Book collections on Project MUSE., 2019)
"In the nineteenth century, George Washington became remembered as a man of the common people and the father of American democracy, despite the fact he was an aristocratic elite who believed in a strong centralized government. Following his death in 1799, the political leaders and social elites of the time competed for control of his memory and symbolic status, seeking to use Washington as a figurehead for their particular cause. But these episodes shed little light on how the greater American populace remembered him. In The Property of the Nation, Matthew Costello tells the story of Washington's tomb, the popularity of which tells us more about how ordinary Americans remembered, shared, and believed in a variety of narratives that made Washington a man of the people. The tomb served as an intersection for historical tourism, race and class relations, popular culture, and religious expression, all facets of life transformed by the growth of political democracy. These experiences illuminate how the democratic impulse transcended the present, as more Americans sought to know, touch, and even possess pieces of Washington's past"--